Optical services over the intelligent optical network. - Benjamin, D. (IEEE Communications magazine)
Optical networks are growing at unprecedented rates to accommodate the explosion in data traffic brought on by new Internet and enterprise applications. Coupled with this growth has been the introduction of client devices (e.g., routers, storage devices, and content servers) at the network edge operating at optical line rates. These two trends are changing the fundamental way in which optical transport networks are being architectured, deployed, and managed. Emerging intelligent optical networks address the traffic scaling challenge. Additionally, when combined with modern service management technologies, these networks open exciting opportunities for delivering new customized optical services directly to end-users, allowing carriers to fully exploit the economics of optical transport. This article presents a network framework for delivering optical services